Fabbrica 4.0: I processi innovativi nel Multiverso fisico-digitale - Lombardi, Mauro (Studi e saggi, 2017)
We have entered the digital era: increasingly powerful computational devices are implemented everywhere and generate increasing flows of information. The digitalization of processes and products implies the combination of different knowledge sources: structured, unstructured, textual, visual and acoustic. Profound and extensive changes emerge: from the design of a good or service to their distribution on the markets and the interactions with consumers. The relationships between the physical and virtual world will be the source of continuous innovations thanks to the pervasiveness of artificial agents with abilities close to the human ones: learning, adaptability, forecasting skills. It is the 'physical-digital universe', which requires new knowledge tools and innovative decision-making strategies.